PROMOTING ENVIRONMENTAL AWARENESS IN LEARNING CONTEXTS - Paradewari, Dirtya S.; Avillanova, Anchieta A.; Lasar, Aloysia B. (International Journal of Humanity Studies (IJHS), 2018)
A bundle of studies in multidisciplinary context has been conducted concerning the earth changes. As we are now witnessing the destruction that our earth is suffering from, promoting environmental awareness becomes visible to be vital. In line with the rapid development of information mobility and technology, English is becoming world’s language. The scope of English users then proved to be continuously in growth. Therefore, English as foreign language (EFL) learning context is considered ideal to promote the environmental awareness. There are some evidence that support the way of promoting the environmental awareness in the educational context. Moreover, Pike and Shelby (1994) point out consciousness in various aspects as the desired result for promoting environmental awareness through education. This paper elaborates those evidence and discusses the aims of global environmental education.DOI: https://doi.org/10.24071/ijhs.2018.010213